Military displays : technology and applications - Desjardins, Daniel D. (SPIE tutorial texts, 2013)
This first-of-its-kind tutorial on military displays begins with a discussion of fundamentals and leads to an understanding of how displays used by the U.S. Armed Forces differ from their counterparts in the civil sector. Advanced undergraduate students, graduate students, beginning display industry professionals, or anyone who wants to know about display fundamentals with an eye to military applications and the military market will benefit from the detailed information herein. In a simple building-block approach, fundamental concepts such as the lumen, luminous intensity, and illuminance are reviewed, and the author progresses with a discussion of the many display technologies, such as CRT, AMLCD, and AMOLED, as well as display subcomponents, such as backlights, polarizers, and dimming circuitry, before ending with an exposition of the military market itself. The latter includes an identification of performance parameter values, not only for the broad arena of fixed- and rotary-wing aircraft, but also tracked and wheeled vehicles, dismounted soldiers, and command and control facilities. This text gives the reader insight to the more than 647 line-replaceable units for display used by these categories of platforms in the U.S. military today.